2002
DOI: 10.1007/s007260200007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The process of wound healing begins immediately following surface lesions or just after exposure to radiation, chemical agents or extreme temperatures. Taurine (2-aminoethane sulfonic acid), an amino acid containing sulfur, is found in almost all tissues in mammals, playing various important physio-logical roles in each organ. Taurine exhibits an antioxidant effect and is also known to have effects on cell proliferation, inflammation and collagenogenesis. Many antioxidants have been used to eliminate the negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Chitosan and its derivatives could accelerate wound healing by enhancing the functions of inflammatory cells, such as polymorphonuclear leukocytes (PMN) [4,2931], macrophages [4,32,33], and fibroblasts [4,3436] or osteolasts [37]. It has also been reported that chitosan could increase the tensile strength of wounds [38]. The wound-healing effects of chitosan could be affected by the factors of molecular weight [33,39,40], deacetylation degree [35,39,40], as well as the state of chitosan [41].…”
Section: Wound-healing Effects Of Chitosan Preparationsmentioning
confidence: 99%
“…Chitosan and its derivatives could accelerate wound healing by enhancing the functions of inflammatory cells, such as polymorphonuclear leukocytes (PMN) [4,2931], macrophages [4,32,33], and fibroblasts [4,3436] or osteolasts [37]. It has also been reported that chitosan could increase the tensile strength of wounds [38]. The wound-healing effects of chitosan could be affected by the factors of molecular weight [33,39,40], deacetylation degree [35,39,40], as well as the state of chitosan [41].…”
Section: Wound-healing Effects Of Chitosan Preparationsmentioning
confidence: 99%
“…Chitosan could accelerate coagulation and enhance the functions of inflammatory cells (13)(14)(15)(16). Moreover, it has been reported that chitosan could increase the tensile strength of wounds (17).…”
mentioning
confidence: 99%
“…In literature, many research studies have investigated the effect of topical insulin administration [18], epidermal growth factor [19], fibroblast growth factor, vitamin E [20,21], selenium [22], and taurine [16] on the healing process of tissue defects that have been created in oral mucosa and on oxidative stress. There are also other research studies that have examined the effects of Lcarnitine on the healing of defects developed on the skin [1,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the method developed by Woessner [15] has been used by implementing various modifications to the method [16]. Standard hydroxyproline was run and values reported as microgram per milligram dry weight of tissue [17].…”
Section: Hydroxyproline Estimationmentioning
confidence: 99%